Case report: A combination of mirror therapy and magnetic stimulation to the sacral plexus relieved phantom limb pain in a patient - Deng, Chunchu; Li, Qian (Frontiers in Neuroscience, 2023)
Phantom limb pain (PLP) is a common sequela of amputation, experienced by 50-80 % of amputees. Oral analgesics as the first-line therapy have limited effects. Since PLP usually affects activities of daily living and the psychological conditions of patients, effective treatments are imperatively needed. In this case study, a 49-year-old man was admitted to our hospital because of uncontrollable paroxysmal pain in his missing and residual leg. Due to severe injuries in a truck accident, the right lower limb of the patient was surgically amputated approximately 5 years ago. Around 1 month after amputation, he felt pain in his lost leg and PLP was diagnosed. Then, he started taking oral analgesics, but the pain still occurred. After admission on July 9, 2022, the patient received treatments of mirror therapy and magnetic stimulation to the sacral plexus. 1-month treatments reduced the frequency and intensity of pain in the phantom limb and the stump, without any adverse events. Analysis of high-resolution three-dimensional T1-weighted brain volume images at the end of 2-month treatments showed alterations in the thickness of cortex regions related to pain processing, compared to that before treatment. This case study gives us hints that one or both interventions of mirror therapy and sacral plexus magnetic stimulation effectively relieved PLP and stump limb pain. These non-invasive, low-cost and easily conducted treatments could be good options for PLP. But randomized controlled trials with a large number of cases are required to confirm their efficacy and safety.